2018
DOI: 10.14419/ijet.v7i2.11.11007
|View full text |Cite
|
Sign up to set email alerts
|

Role of Social Media Optimization in Digital Marketing with special reference to Trupay

Abstract: Social media optimization has been used by many organizations in the recent years, after the growth of Internet, for enhancing the growth and profits of their business. This paper discusses some of the strategies of digital marketing adopted by Trupay after the period of demonetization in India.SMO (Social Media Optimization) can be defined as the process of increasing the popularity and awareness of the product in the minds of the people. It is basically a marketing tool which helps in the promotion, marketin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
1
5
0
2
Order By: Relevance
“…Sahai et al. (2018) researched the usage of the Indian fintech service, TruePay, and found that social media played a significant role in TruePay's success.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sahai et al. (2018) researched the usage of the Indian fintech service, TruePay, and found that social media played a significant role in TruePay's success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Topic modeling was conducted to identify the trends of fintech and to analyze the contents of fintech. Sahai et al (2018) researched the usage of the Indian fintech service, TruePay, and found that social media played a significant role in TruePay's success. In particular, Facebook's TruePay page showed the largest traffic compared to other marketing channels.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced marketing will build customer trust in business. One might say that practically all clients who need to purchase an item or pick a help will check the data accessible on the web (Sahai et al, 2018). They will check through sites, Instagram accounts, Facebook, Twitter, and other social stages that might have the option to give reliable data and content.…”
Section: Digital Marketing In Businessmentioning
confidence: 99%
“…Di dalam literatur tidak ditemukan defisini secara formal tentang SMO. Namun penelitian ini mengadopsi konsep dari Sahai-Goel yang mendefinisikan SMO sebagai salah satu teknik internet marketing dengan memanfaatkan media sosial sebagai saran untuk meningkatkan trafik sebuah website atau menumbuhkan kesadaran akan sebuah produk, media promosi, atau suatu kegiatan kepada konsumen secara luas dan efisien [8].…”
Section: Pendahuluanunclassified
“…Penggunaan SMO sebagai salah satu teknik untuk meningkatkan trafik kunjungan web seiring dengan semakin populernya sosial media di kalangan pengguan internet terutama pembeli online. Hal ini sesuai dengan saran dari para ahli di bidang digital marketing, bahwa teknik SMO sangat efektif membantu meningkatkan popularitas serta branding suatu produk [8][9][10]. Hal yang sama juga dinyatakan dalam penelitian yang dilakukan oleh Rossmann dan Young bahwa hasil penerapan SMO yang telah dilakukan menunjukkan adanya peningkatan terhadap lalu lintas web dan media sosial ke halaman website [11].…”
Section: Pendahuluanunclassified